Service Quality and Price Perception Increase Indrive Customer Satisfaction - Cantika Putri Utami; Widiya Avianti (Trescode Green Organization, 2024)
The purpose of this study is to analyze the influence of service quality and price perception on customer satisfaction of InDrive users (Case study of the Palinggihan Plered Purwakarta Village Community). This research method uses a quantitative method with a survey method. The number of samples in this study is 277 people, the data processing in this study uses the SmartPLS 3.0 analysis tool. The analysis used in this study includes the analysis of the outer model and the inner model. The results of this study show that, (1) service quality has a positive and significant effect on customer satisfaction, (2) price perception has a positive and significant effect on customer satisfaction, (3) the R-Square value has an effect between service quality variables and price perception on customer satisfaction by 0.469 or 46.9% which means a moderate model.